WISATA PERKOTAAN SEBAGAI KONSEP PENGEMBANGAN PUSAT AKTIVITAS TRANSIT RAWA BOKOR - Juan Angelo; Nafiah Solikhah (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
The Rawa Bokor area which is located in Benda District, Tangerang City is directly adjacent to Soekarno-Hatta International Airport and the City of Jakarta, so it has great potential to not only improve the image of Tangerang City in the national eye, but also internationally and has the potential to improve the economic conditions of the surrounding population. . From this potential, it can be seen that in the future, the Rawa Bokor Area can become a place to capture transit activities that can support Soekarno-Hatta International Airport. Although it has potential as a transit supporter, the existing condition of the area currently only has accommodation and is not sufficient to accommodate transit activities that are more than just resting, such as a quick exploration container while waiting for flight hours. To respond to these problems, the approach used is the Urban Acupuncture method, with a focus on Urban Tourism. The program concept that is suitable for the characteristics of transit activities in the Rawa Bokor area is Sightseeing Tourism, and uses Biophilic Architecture and Sustainable Building as design references. This is because the Bokor Swamp Area has several other shortcomings, such as insufficient vegetated land, and most buildings in this area are not feasible (not sustainable). The main program produced is the Contemporary Art Gallery and supporting programs such as Local Retail Area, Indoor – Outdoor Spa, and Workspace, which are expected to provide visitors from abroad and within the country a place for exploration, relaxation, rest, and other transit activities. , so as to improve the image of the City of Tangerang, as well as the economic conditions of this area and its surroundings. Keywords:  Activity; Airport; Gallery; Potency; Tourism Abstrak Daerah Rawa Bokor yang terletak di Kecamatan Benda, Kota Tangerang berbatasan langsung dengan Bandara Internasional Soekarno-Hatta dan Kota Jakarta, sehingga berpotensi besar untuk tidak hanya meningkatkan citra Kota Tangerang di mata nasional, tetapi juga di mata internasional serta berpotensi untuk meningkatkan kondisi ekonomi penduduk sekitar. Dari potensi tersebut dapat dilihat bahwa pada masa yang akan datang, Daerah Rawa Bokor dapat menjadi sebuah wadah untuk menangkap aktivitas transit yang dapat mendukung Bandara Internasional Soekarno-Hatta.  Meskipun memiliki potensi sebagai pendukung transit, kondisi eksisting daerah saat ini hanya memiliki tempat penginapan dan tidak cukup untuk menampung aktivitas transit yang lebih dari sekedar beristirahat, seperti wadah eksplorasi secara cepat ketika menunggu jam terbang. Untuk menanggapi permasalahan tersebut, pendekatan yang digunakan adalah metode Urban Aqupuncture, dengan fokus Urban Tourism. Konsep program yang cocok pada karakteristik aktivitas transit Daerah Rawa Bokor adalah Sightseeing Tourism, dan menggunakan Biophilic Architecture dan Sustainable Building sebagai acuan desain. Hal ini dikarenakan Daerah Rawa Bokor memiliki beberapa kekurangan lainnya seperti lahan vegetasi yang kurang, dan kebanyakan bangunan pada daerah ini sudah tidak layak (tidak sustain). Program utama yang dihasilkan adalah Contemporary Art Gallery dan program pendukung seperti Local Retail Area, Indoor – Outdoor Spa, dan Workspace, yang diharapkan dapat memberikan pengunjung baik dari luar maupun dalam negeri sebuah wadah untuk aktivitas eksplorasi, bersantai, istirahat, dan kebutuhan kegiatan transit lainnya, sehingga dapat meningkatkan citra Kota Tangerang, juga kondisi perekonomian daerah ini dan sekitarnya.